Anchoring eccentricity features and rectifying devices for resin grouted bolt/cable bolt - Liu, Shaowei; He, Deyin; Jia, Housheng; Fu, Mengxiong; Hou, Biao (International journal of mining science and technology, 2022)
The anchoring eccentricity of the bolt and cable bolt is a common problem in geotechnical support engineering and affects the ability of the bolt and cable bolt to control the rock mass to a certain extent. This paper reports on numerical simulation and laboratory experiments conducted to clarify the effect of eccentricity on the anchoring quality of the bolt and cable bolt, and to establish an effective solution strategy. The results reveal that the anchoring eccentricity causes unbalanced stress distribution and the uncoordinated deformation of the resin layer, which results in higher stress and greater deformation of the resin layer at the near side of the rod body. Additionally, as the degree of anchoring eccentricity increases, the effect becomes more significant, and the resin layer of the anchoring system becomes more likely to undergo preferential failure locally, which weakens the load-bearing performance of the anchoring system. This paper develops an innovative bolt anchoring rectifying device (B-ARD) and cable bolt anchoring rectifying device (C-ARD) on the basis of the structural characteristics of the bolt and cable bolt to better ensure the anchoring effect of them. The working effects of these two devices were verified in detailed experiments and analysis. The experimental results show that the anchoring rectifying devices (ARD) improve and ensure the anchoring concentricity of the bolt and cable bolt, which will help improve the supporting performance of them. The paper provides a convenient and effective method for improving the anchoring concentricity of the bolt and cable bolt, and provides a concept and reference for technical research on improving the effect of roof bolting.